2018
DOI: 10.1128/iai.00387-17
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis GroEL2 Modulates Dendritic Cell Responses

Abstract: successfully subverts the host immune response to promote disease progression. In addition to its known intracellular niche in macrophages, interferes with the functions of dendritic cells (DCs), which are the primary antigen-presenting cells of the immune system. We previously showed that dampens proinflammatory responses and impairs DC functions through the cell envelope-associated serine protease Hip1. Here we present data showing that GroEL2, a substrate of Hip1, modulates DC functions. The full-length Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…Other groups of glycoproteins involved in M.tb –host interactions are the ones belonging to the MCE family, MPT64, or Apa, among others, involved in colonization and invasion of host cells ( Sonawane et al, 2012 ), as well as other proteins such as Rv0227c, HtrA-like serine protease Rv1223, TatA, GlnA1, and the disulfide oxidase DsbA-like enzyme Rv2969c, recently described as mannosylated ( Tonini et al, 2020 ). In addition, GroEL2, a chaperone-like M.tb capsule-associated glycoprotein, is shown to contribute to the suboptimal antigen presentation during mycobacterial infection by modulating macrophage and DC proinflammatory responses ( Georgieva et al, 2018 ), supporting the immunogenic role of M.tb cell envelope-associated glycoproteins during M.tb infection. Other strategies used by M.tb to counteract host defense mechanisms are the blockade of phagolysosome biogenesis and phagosomal acidification, where cell envelope components such as ManLAM and TDM among others, play important roles ( Fratti et al, 2003 ; Vergne et al, 2004 ; Kang et al, 2005 ) ( Table 1 ).…”
Section: Adaptation Of Drug-resistant Mtb Strainsmentioning
confidence: 99%
“…Other groups of glycoproteins involved in M.tb –host interactions are the ones belonging to the MCE family, MPT64, or Apa, among others, involved in colonization and invasion of host cells ( Sonawane et al, 2012 ), as well as other proteins such as Rv0227c, HtrA-like serine protease Rv1223, TatA, GlnA1, and the disulfide oxidase DsbA-like enzyme Rv2969c, recently described as mannosylated ( Tonini et al, 2020 ). In addition, GroEL2, a chaperone-like M.tb capsule-associated glycoprotein, is shown to contribute to the suboptimal antigen presentation during mycobacterial infection by modulating macrophage and DC proinflammatory responses ( Georgieva et al, 2018 ), supporting the immunogenic role of M.tb cell envelope-associated glycoproteins during M.tb infection. Other strategies used by M.tb to counteract host defense mechanisms are the blockade of phagolysosome biogenesis and phagosomal acidification, where cell envelope components such as ManLAM and TDM among others, play important roles ( Fratti et al, 2003 ; Vergne et al, 2004 ; Kang et al, 2005 ) ( Table 1 ).…”
Section: Adaptation Of Drug-resistant Mtb Strainsmentioning
confidence: 99%
“…This penetration leads to a disruption of DCs activity by prompting the production of interleukin (IL)-10 and reducing the production of IL-12, thus causing a suppression of T lymphocytes activity (33, 34). The manipulation of the maturation of the DCs probably represents one of the winning strategies of Mbt that, by restraining the activity of DCs and, consequently, of T lymphocytes, allows the Mtb, whose speed of growth is relatively slow, to efficiently establish a bridgehead in the airways (35). Based on the above mentioned mechanism DC-SIGN has recently been proposed as a potential target for a vaccine purpose eventually able to enhance immunity against Mtb (36).…”
Section: Innate Immune Response Against Mycobacterium Tuberculosismentioning
confidence: 99%
“…Lastly, M. tuberculosis can also impair innate immune responses to cell-envelope components through enzymatic means. For instance, an M. tuberculosis serine-hydrolase, Hip1, was found to cleave multimeric, cell-wall associated GroEL2 to a secreted monomeric form to mediate attenuated macrophage and dendritic cell (DC) responses(105109). Additionally, M. tuberculosis mutants lacking hip1 or a putative mycobacterial metalloprotease, zmp1 , display enhanced inflammasome activation(106, 110), suggesting that M. tuberculosis contain multiple strategies for dampening activation of the inflammasome.…”
Section: Innate Immunity To M Tuberculosis Infectionmentioning
confidence: 99%
“…Additionally, M. tuberculosis promotes suboptimal antigen presentation in vitro and in vivo without detectable differences in the expression levels of costimulatory molecules when compared to BCG infected DCs(266). Interestingly, studies using a mutant M. tuberculosis strain lacking hip1 (discussed above) indicate that M. tuberculosis readily impairs DC costimulation and cytokine production to evade antigen-specific CD4 T-cell responses(107, 109) and a recent study demonstrated that BCG hip1 retains similar immune evasion functions(267). Taken together, the initiation of the adaptive immune response requires the participation of DCs, which themselves are readily infected and subverted by M. tuberculosis infection.…”
Section: Innate Immunity To M Tuberculosis Infectionmentioning
confidence: 99%